Base-Controlled One-Pot Chemoselective Suzuki–Miyaura Reactions for the Synthesis of Unsymmetrical Terphenyls - Li, Xinmin; Feng, Fangfang; Ren, Changyue; Teng, Yong; Hu, Qinghong; Yuan, Zeli (Synlett, 2019)
We report a chemoselective Suzuki–Miyaura reaction protocol of using bromophenyl fluorosulfonate as building block for the preparation of unsymmetrical terphenyls. The chemoselective cross-coupling of bromophenyl fluorosulfonate and arylboronic acids can be achieved by controlling base species without using any ligands. Under this methodology, various of m- and p-unsymmetrical terphenyls were obtained in moderate to good yields.
Keywords: chemoselective; Suzuki–Miyaura reactions; unsymmetrical terphenyls; one-pot; ligand-free